Full‐Color Tunable Circularly Polarized Luminescent Nanoassemblies of Achiral AIEgens in Confined Chiral Nanotubes. Issue 19 (10th March 2017) - Han, Jianlei; You, Jing; Li, Xianggao; Duan, Pengfei; Liu, Minghua
Abstract : Circularly polarized luminescent (CPL) materials are currently attracting great interest. While a chiral building is usually necessary in order to obtain CPL materials, here, this study proposes a general approach for fabricating 1D circularly polarized luminescent nanoassemblies from achiral aromatic molecules or aggregation‐induced emissive compounds (AIEgens). It is found that a C 3 symmetric chiral gelator can individually form hexagonal nanotube structures and encapsulate the guest molecules. When achiral AIEgens are encapsulated into the confined nanotubes via organogelation, the AIEgens will emit circularly polarized luminescence. Further, the direction of the CPL could be controlled by the supramolecular chirality of the nanotube. Remarkably, the approach is universal and various kinds of the AIEgens can be doped to show such property, providing a full‐color‐tunable circularly polarized luminescence. Abstract : Circularly polarized luminescence is observed from achiral dyes doped in confined chiral nanotube organogels which are assembled from C 3 symmetric chiral gelators with hexagonal tubular structures. This provides a versatile approach for fabricating 1D circularly polarized luminescent materials.